An application of multi-dimensional matching to logistics - Exoo, Geoffrey; Jiang, Jianling; Zhao, Cheng (Utilitas Mathematica, 2000)
We investigate a problem that arose in transportation engineering that can be solved as a multi-dimensional matching problem. Some approximation algorithms for solving such problems are compared. A related asymptotic result is also presented.